ROLE OF SPECIAL EDUCATION CURRICULUM IN ADJUSTMENT OF PHYSICALLY HANDICAPPED CHILDREN IN SOCIETY - Malik, Shazia; Abdul Manaf, Umi Kalthom (PEOPLE: International Journal of Social Sciences, 2015)
The purpose of this study was to identify the role of the special education curriculum in adjustment of physically handicapped children in society. The researcher used self developed questionnaires to collect the data about the problem under investigation. All physically handicapped children of District Lahore were constituted as target population for the study. The physically handicapped children of Special Education School, Lahore were assessable population for the study. Fifty physically handicapped children from Special Education School Lahore were conveniently selected as a sample for the study. Simple descriptive statistical techniques such as mean and percentages were used to analyze the collected data. After careful data analysis the researcher concluded that the special education curriculum may play very vital role in the adjustment of physically handicapped children in society but unfortunately due to lack of resources and infrastructure and lack of teachers trainings that need to involve parents in education and rehabilitation program. Trained and qualified teachers should be appointed in these schools. There is also some lack in the awareness about the importance of social adjustment of physically handicapped children in the society. The researchers identified very important needs, problems, and adjustment problems of physically handicapped children through review of literature and research.